“Omics” insights into plastid behavior toward improved carotenoid accumulation - Li, Yuanyuan; Jian, Yue; Mao, Yuanyu; Meng, Fanliang; Shao, Zhiyong; Wang, Tonglin; Zheng, Jirong; Wang, Qiaomei; Liu, Lihong (Frontiers in Plant Science, 2022)
Plastids are a group of diverse organelles with conserved carotenoids synthesizing and sequestering functions in plants. They optimize the carotenoid composition and content in response to developmental transitions and environmental stimuli. In this review, we describe the turbulence and reforming of transcripts, proteins, and metabolic pathways for carotenoid metabolism and storage in various plastid types upon organogenesis and external influences, which have been studied using approaches including genomics, transcriptomics, proteomics, and metabonomics. Meanwhile, the coordination of plastid signaling and carotenoid metabolism including the effects of disturbed carotenoid biosynthesis on plastid morphology and function are also discussed. The “omics” insight extends our understanding of the interaction between plastids and carotenoids and provides significant implications for designing strategies for carotenoid-biofortified crops.